2019
DOI: 10.1002/ijc.32334
|View full text |Cite
|
Sign up to set email alerts
|

SET domain containing 1B gene is mutated in primary hepatic neuroendocrine tumors

Abstract: Primary hepatic neuroendocrine tumors (PHNETs) are extremely rare NETs originating from the liver. These tumors are associated with heterogeneous prognosis, and few treatment targets for PHNETs have been identified. Because the major genetic alterations in PHNET are still largely unknown, we performed whole-exome sequencing of 22 paired tissues from PHNET patients and identified 22 recurring mutations of somatic genes involved in the following activities: epigenetic modification (BPTF, MECP2 and WDR5), cell cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
2
11
1
Order By: Relevance
“…At present, the pathogenesis of PHNET is still unclear, and three hypotheses about its origin have been proposed [9] : 1. from the multifunctional stem cells of the liver; 2. caused by the proliferation of neuroendocrine cells in the intrahepatic bile duct epithelium; and 3. from other ectopic tissues with endocrine functions. A recent study showed that mutations in the SET domain of the 1B gene might be related to the occurrence of PHNETs [10] .…”
Section: Discussionmentioning
confidence: 99%
“…At present, the pathogenesis of PHNET is still unclear, and three hypotheses about its origin have been proposed [9] : 1. from the multifunctional stem cells of the liver; 2. caused by the proliferation of neuroendocrine cells in the intrahepatic bile duct epithelium; and 3. from other ectopic tissues with endocrine functions. A recent study showed that mutations in the SET domain of the 1B gene might be related to the occurrence of PHNETs [10] .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent whole-exome sequencing analysis involving 22 samples of PHNETs from 26 hospitals, 11 mutation of SETD1B was identified as a potential cause of and a diagnostic or prognostic molecular marker for PHNETs. Clinically, PHNETs are distinctive from NENs of other organs because the vast majority of PHNETs do not produce the clinical manifestations of increased neuroendocrine hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Signi cantly mutated gene (SMG) analysis identi ed several genes including SETD1B, RNF43, MBD6 and so on, whose mutation states were profoundly in uenced by NEB mutation. SETD1B mutation was associated with intellectual disability, epilepsy and autism (21), and was also found to be mutated in primary hepatic neuroendocrine (22), hepatocellular (23), gastric and colorectal tumors (24). RNF43 is a tumour suppressor gene that frequently mutated in colorectal and endometrial cancers (25,26).…”
Section: Discussionmentioning
confidence: 99%